Utilización de antiinfecciosos en pacientes hospitalizados en el servicio de pediatría del Hospital Belén de Trujillo enero – marzo 2007 - Domínguez Chinchayhuara, Ronal (2007)
Objective: To describe the antiinfectious characteristics of use of (ATM) in the service of hospital of Pediatría of the Belen Hospital of Trujillo. Material and Methods: A descriptive, cross-sectional, prospective. The population sample was shaped by the medical prescriptions of the patients hospitalized in the service of pediatrics January - March of the 2007. This service counts on a total of 28 beds. Results: 184 patients and their respective clinical histories included themselves. The prevalence of the prescription of antiinfectious (PPA) was 72,28%. The average of prescription of antiinfectious by hospitalized patient was 1.5. The profile of consumption of antiinfectious based on DDP/100camas-day, by farmacológico group demonstrating to Cefalosporins (44.22%), Penicillins (32.39%) and Aminoglucosides (10.22%), with greater consumption. The proportion of antiinfectious prescribed with prophylactic and therapeutic intention was 36,09% and 63,91% respectively. Prescribed 95% of the antiinfectious ones belong to Petitorio Nacional Medicamentos Esenciales (PNME). The greater consumed cost of antiinfectious corresponds to cefotaxima with 26,91% of the total cost. Conclusions: The PPA and average of antiinfeccisos by patient are within the ranks reported in other studies; the greater antiinfectious evidence to Cefalosporinas ,Penicillins and Aminoglucosides consumption of; The proportion of antiinfectious prescribed with prophylactic and therapeutic intention is within the published accepted values in other studies, most of antiinfectious used belongs to the PNME, on the other side cefotaxima represents the one of greater consumed cost of total of antiinfectious